Current collector, pole piece, secondary battery, electric device, copper foil and preparation method of copper foil
By using copper foil with an average particle size of 50nm-400nm, combined with a high proportion of nanotwin structure and pulse current deposition technology, the problem of the secondary battery current collector is easily broken under high expansion force, and the high tensile strength and elongation of the copper foil are achieved, and the energy density and safety performance of the secondary battery are improved.
Patent Information
- Application Number
- CN202410146761.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-01
- Publication Date
- 2025-04-18
AI Technical Summary
The current collector of existing secondary battery is prone to fracture under high expansion force, resulting in limited safety accidents and electrochemical performance improvement, making it difficult to meet the needs of the new generation of high-energy density secondary batteries.
The copper foil with an average particle size of 50nm-400nm is used, and the number of nanotwin crystal grains in the copper foil accounts for no less than 60%. It is prepared by electroplating method and combined with pulse current deposition technology to control the grain size and structure, and improve the mechanical strength and plasticity of the copper foil.
It significantly improves the tensile strength and elongation of breaking of copper foil, and can be suitable for secondary batteries with high expansion force, improving the energy density and safety performance of the battery.
Smart Images

Figure CN119852418A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of battery technology, and specifically relates to a current collector, a pole piece, a secondary battery, an electrical device, a copper foil, and a method for preparing the copper foil. Background Art
[0002] In recent years, secondary batteries have been widely used in energy storage power systems such as hydropower, thermal, wind and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields.
[0003] The current collector is an important component of secondary batteries. As the market's requirements for the energy density and safety performance of secondary batteries increase, it is urgent to develop a light and high-strength current collector to meet the needs of the new generation of secondary batteries. Summary of the invention
[0004] The present application is made in view of the above-mentioned problems, and its purpose is to provide an extremely thin current collector with excellent mechanical properties to meet the requirements of the current collector for the new generation of high-performance batteries.
[0005] In order to achieve the above-mentioned purpose, the present application provides a current collector, a pole piece, a secondary battery, an electrical device, a copper foil and a method for preparing the copper foil.
[0006] In a first aspect, the present application provides a current collector, which includes a copper foil, wherein the average particle size of the grains in the copper foil is 50nm-400nm, and based on the total number of grains in the copper foil, the number of nanotwin grains accounts for no less than 60%.
[0007] Twin structure is an effective means to improve the strength and plasticity of metals. The twin boundary is a coherent interface with neatly arranged atoms, which can increase the strength of the material by increasing the resistance to dislocation movement while maintaining the mobility of dislocations, thereby strengthening the material while maintaining the plasticity of the material. Small grain size can further increase the interface structure, increase the external stress required for dislocations to pass through the grain boundary, and achieve material strengthening. The high proportion of nano-twin structure and small grain size work together to improve the mechanical strength of copper foil while maintaining its high plasticity, providing a material basis for further improvement of battery energy density and safety.
[0008] In any embodiment, the average grain size of the copper foil is 50 nm to 300 nm.
[0009] Copper foil with an average particle size within the above range can further improve its mechanical strength while maintaining its high plasticity, meeting the use requirements of a new generation of high energy density secondary batteries.
[0010] In any embodiment, based on the total number of grains in the copper foil, the number of grains with a particle size less than 200 nm accounts for 20%-40%, and the number of grains with a particle size between 200 nm and 500 nm accounts for 50%-80%.
[0011] In any embodiment, based on the total number of grains in the copper foil, the number of grains with a grain size greater than 500 nm accounts for less than or equal to 5%.
[0012] In the prior art, copper foil strengthened by twinning often introduces micron-sized twins during the preparation process, which hinders the further improvement of the strength of the copper foil. The copper foil provided in the embodiment of the present application has a high proportion of nano twins, which significantly improves the strength of the copper foil, and the grains have a small average particle size, and the particle size is skewed. The number of grains with a particle size greater than 500nm accounts for a very small proportion. The fine grains reduce the occurrence of concentrated stress during the deformation of the copper foil, and are more conducive to the coordinated sliding of the grains. Therefore, the elongation at break can be improved while the strength of the copper foil is improved.
[0013] In any embodiment, based on the total number of grains in the copper foil, the number of equiaxed grains or quasi-equiaxed grains accounts for greater than or equal to 80%, and the length ratio a1 of the major axis to the minor axis of the equiaxed grains or quasi-equiaxed grains satisfies: 1≤a1<2.
[0014] A large number of equiaxed grains or quasi-equiaxed grains are beneficial to achieving the isotropy of the copper foil in all directions, and are beneficial to comprehensively improving the strength and plasticity of the copper foil.
[0015] In any embodiment, based on the total number of grains in the copper foil, the number of columnar grains accounts for less than 10%, and the ratio a2 of the length of the major axis to the minor axis of the columnar grains satisfies: a2>2.
[0016] The formation of columnar grains can easily lead to the heterogeneity of the mechanical properties of copper foil. Reducing the proportion of columnar grains is beneficial to improving the mechanical strength and plasticity of copper foil and reducing the probability of forming stress concentration points.
[0017] In any embodiment, the crystal plane diffraction intensity of the (111) texture in the copper foil accounts for 60%-85% of the total crystal plane diffraction intensity of the (111) texture, (200) texture, (220) texture, (311) texture, and (222) texture in the copper foil.
[0018] For pure copper materials, common textures include (111), (200), (220), (311), and (222). According to crystallographic properties, the (111) crystal plane has a high atomic density and high mechanical strength, which can improve the twin strengthening effect. Copper foils with a ratio of the crystal plane diffraction intensity of the (111) texture to the sum of the crystal plane diffraction intensities of the (111) texture, (200) texture, (220) texture, (311) texture, and (222) texture in the copper foil within the above range are beneficial to improving the mechanical strength and plasticity of the copper foil.
[0019] In any embodiment, the copper foil has a first surface and a second surface relative to each other, the thickness of the copper foil is denoted as H, the area from the first surface of the copper foil to the thickness range of 0.2H-0.5H is recorded as the first area of the copper foil, and the area from the second surface of the copper foil to the thickness range of 0.2H-0.5H is recorded as the second area of the copper foil, and the absolute value of the difference between the average particle size of the grains in the first area and the average particle size of the grains in the second area is less than or equal to 150nm.
[0020] The grain size and structure of the copper foil are also highly uniform along the thickness direction of the copper foil, providing a basis for it to maintain high strength and high plasticity while having ultra-thin thickness.
[0021] In any embodiment, based on the total number of grains in the copper foil, the number of nano twins accounts for 65% to 90%.
[0022] In any embodiment, the maximum surface roughness of the copper foil is less than or equal to 3 μm.
[0023] Copper foil with a maximum surface roughness not exceeding 3μm has a smooth and uniform surface, and is not easy to form stress concentration points during cyclic stress, which is beneficial to improving the mechanical strength and plasticity of the copper foil.
[0024] In any embodiment, the thickness H of the copper foil satisfies: 3 μm≤H≤15 μm.
[0025] The copper foil has a low thickness, which can effectively reduce the weight of the battery and is conducive to further improving the energy density of the battery.
[0026] In any embodiment, under the test conditions of room temperature, sample thickness of 6±0.2 μm, and tensile speed of 50±0.5 mm / min, the tensile strength of the copper foil is greater than or equal to 600 MPa and the elongation at break of the copper foil is greater than or equal to 4%.
[0027] In any embodiment, under the test conditions of room temperature, sample thickness of 6±0.2 μm, and tensile speed of 50±0.5 mm / min, the tensile strength of the copper foil is 700 MPa-1500 MPa; and the elongation at break of the copper foil is 4.5%-10%.
[0028] The copper foil has both high strength and high plasticity, which can meet the use requirements of high energy density batteries, improving the safety of the battery while increasing the energy density of the battery.
[0029] A second aspect of the present application provides a pole piece, comprising a current collector in any embodiment.
[0030] A third aspect of the present application provides a secondary battery, comprising the electrode sheet of the second aspect.
[0031] In any embodiment, the secondary battery is any one of a battery cell, a battery module, and a battery pack.
[0032] In any embodiment, the maximum expansion force of the secondary battery cell is greater than or equal to 1000 kgf.
[0033] In any embodiment, the maximum expansion force of the secondary battery cell is greater than or equal to 2500 kgf.
[0034] In any embodiment, the maximum expansion force of the secondary battery cell is greater than or equal to 4000 kgf. The current collector in the prior art is prone to breakage under the high expansion force of the secondary battery, causing safety accidents and limiting the further improvement of the electrochemical performance of the secondary battery. The current collector provided in the embodiment of the present application has excellent tensile strength and elongation at break, can be applied to secondary batteries with high expansion force, and is conducive to further improving the energy density of the secondary battery.
[0035] A fourth aspect of the present application provides an electrical device, comprising the secondary battery of the third aspect.
[0036] The fifth aspect of the present application provides a method for preparing copper foil, which is prepared by electroplating. The electroplating method specifically includes periodically applying current to an electrolyte to reduce and deposit copper ions in the electrolyte to form copper foil. The average particle size of grains in the copper foil is 50nm-400nm, and based on the total number of grains in the copper foil, the number of nanotwin grains accounts for greater than or equal to 60%.
[0037] In any embodiment, the current is a pulse current, and the pulse current includes one or more of a square wave pulse current, a sine wave pulse current, a triangle wave pulse current, and a sawtooth wave pulse current.
[0038] Applying pulse current to the electrolyte can control the process of nucleation and grain growth of reduced copper ions by turning the current on and off, thereby inhibiting grain growth and forming uniform nano-grains to improve the tensile strength and elongation at break of the copper foil. Compared with the DC current deposition commonly used in the prior art, pulse current deposition can achieve a higher peak current density, which is conducive to the nucleation of a large number of copper foils to increase the density of the copper foil and reduce the grain size of the copper foil to improve the mechanical strength of the copper foil.
[0039] In any embodiment, the electrolyte includes an additive, and the additive includes one or more of a leveling agent, a wetting agent, and a brightener.
[0040] In any embodiment, the additives include leveling agents, wetting agents, and brighteners.
[0041] The leveling agent can adhere to the tip of the aluminum foil with a fast deposition rate, inhibit the growth of grains, balance the growth rate of pits and tips, and improve the flatness of the aluminum foil. The wetting agent can improve the wettability of the electrolyte and the substrate. The wettability of the electrolyte on the cathode is sufficient to achieve rapid electrodeposition with a large current, increase the nucleation rate of the copper foil, and reduce the average particle size of the grains in the copper foil. A certain amount of brightener can make the grain size of the copper foil smaller, reduce the surface roughness of the copper foil, and improve the smoothness of the surface.
[0042] In any embodiment, the concentration of the leveler in the electrolyte is 20 mg / L-300 mg / L.
[0043] In any embodiment, the concentration of the leveler in the electrolyte is 50 mg / L-150 mg / L.
[0044] In any embodiment, the concentration of the wetting agent in the electrolyte is 10 mg / L-200 mg / L.
[0045] In any embodiment, the concentration of the wetting agent in the electrolyte is 30 mg / L-100 mg / L.
[0046] In any embodiment, the concentration of the brightener in the electrolyte is 10 mg / L-200 mg / L.
[0047] In any embodiment, the concentration of copper ions in the electrolyte is 30 g / L-100 g / L.
[0048] In any embodiment, the concentration of copper ions in the electrolyte is 45 g / L-75 g / L.
[0049] The research results show that the combination of low copper ion concentration and high additive concentration is more conducive to comprehensively improving the strength and elongation at break of copper foil than the combination of high copper ion concentration and low additive concentration. In addition, low copper ion concentration helps to reduce concentration polarization, control the growth and deposition rate of grains, and is conducive to the preparation of small-sized grains and the improvement of the mechanical strength of copper foil.
[0050] In any embodiment, the concentration of chloride ions in the electrolyte is 10 mg / L-80 mg / L.
[0051] In any embodiment, the pH of the electrolyte is 2.5-4.4.
[0052] In any embodiment, the leveling agent includes one or more of gelatin and Janus Green; the wetting agent includes one or more of hydroxyethyl cellulose and polyethylene glycol; the brightening agent includes one or more of sodium polydisulfide propane sulfonate, sodium 3-mercapto-1-propane sulfonate, and thiourea.
[0053] In any embodiment, the wetting agent comprises hydroxyethylcellulose and polyethylene glycol.
[0054] The results show that adding two different wetting agents at the same time can more effectively improve the mechanical strength of copper foil than adding a single type of wetting agent. Although the mechanism is not clear, it is speculated that it may be related to the competitive adsorption of two different types of additives, which is beneficial to improve the consistency of grains during the deposition process, reduce the difference in grain size in the thickness direction, and improve the uniformity of copper foil.
[0055] In any embodiment, the mass concentration ratio of the copper ion to the leveling agent is 500:1-4500:1; and / or the mass concentration ratio of the copper ion to the brightener is 300:1-6000:1.
[0056] In some embodiments, the electrolyte includes gelatin at a concentration of 20 mg / L-150 mg / L, polyethylene glycol at a concentration of 15 mg / L-100 mg / L, hydroxyethyl cellulose at a concentration of 10 mg / L-80 mg / L, sodium polydisulfide dipropane sulfonate at a concentration of 15 mg / L-150 mg / L, copper ions at a concentration of 45 g / L-90 g / L, and chloride ions at a concentration of 10 mg / L-80 mg / L.
[0057] In any embodiment, the peak current density of the pulse current is I, in A / dm 2 The current duty cycle of the pulse current is s, and the peak current density I and the duty cycle s satisfy: 2A / dm 2 ≤I×s≤18A / dm 2 .
[0058] The product of the peak current density I and the duty cycle s is equivalent to the average density of the current within the pulse period. The pulse deposition method allows the average current density within the pulse period to be higher than the maximum current density achievable during DC deposition, because too high a DC deposition density will cause hydrogen evolution and concentration polarization in the electrolyte, reducing the uniformity of the copper foil during the electrodeposition process. The product of the peak current density I and the duty cycle s within the above range can not only effectively reduce the grain size, but also improve the uniformity of the grain size in the thickness direction of the prepared copper foil. The product of the peak current density I and the duty cycle s within the above range, combined with a low copper ion concentration in the electrolyte, can further improve the concentration polarization phenomenon of the electrolyte, achieve the preparation of small-sized grains, and improve the tensile strength and elongation at break of the copper foil. In any embodiment, the peak current density I of the pulse current satisfies: 3.3A / dm 2 ≤I≤333A / dm 2 .
[0059] In any implementation manner, the duty cycle s of the pulse current satisfies: 2%≤s≤50%.
[0060] In any embodiment, the pulse width of the pulse current is 1 ms to 50 ms.
[0061] In any embodiment, the distance between the cathode electrode and the anode electrode is 15 mm to 20 mm.
[0062] In any embodiment, the deposition temperature is 45°C-60°C.
[0063] In any embodiment, the deposition time is greater than or equal to 80 s.
[0064] In any embodiment, the electroplating method specifically includes periodically applying a pulse current to the electrolyte to reduce and deposit the copper ions in the electrolyte; wherein the peak current density I of the pulse current satisfies 100A / dm 2 ≤I≤180A / dm 2 The duty cycle s of the pulse current satisfies: 2%≤s≤10%, and the deposition time is 80s-250s.
[0065] In any embodiment, the preparation method is a continuous production method.
[0066] A sixth aspect of the present application provides a copper foil, which includes the same features as the copper foil in the aforementioned current collector, which will not be repeated here.
[0067] In any embodiment, the copper foil is prepared by the preparation method of the fifth aspect.
[0068] In any embodiment, the maximum width of the copper foil is greater than or equal to 1.5 meters, and / or the maximum length of the copper foil is greater than or equal to 10,000 meters.
[0069] The copper foil can be manufactured in large sizes and has the prospect of industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0070] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some implementation methods of the present application, and for ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.
[0071] Figure 1 is a schematic diagram of the grain size distribution of the copper foil of Example 1 of the present application;
[0072] Figure 2 is an inverse pole figure distribution diagram of the electron backscatter diffraction image of the copper foil of Example 1 of the present application;
[0073] Figure 3 is a tensile curve diagram of the copper foil of Example 1 of the present application;
[0074] Figure 4 a is an X-ray diffraction pattern of the copper foil of Example 2 of the present application; Figure 4 b is an X-ray diffraction pattern of the copper foil of Comparative Example 1 of the present application;
[0075] Figure 5 is a schematic diagram of an embodiment of a secondary battery of the present application;
[0076] Figure 6 is an exploded schematic diagram of an embodiment of a secondary battery of the present application;
[0077] Figure 7 is a schematic diagram of an embodiment of a battery module of the present application;
[0078] Figure 8 is a schematic diagram of an embodiment of a battery pack of the present application;
[0079] Fig. 9 yes Figure 8 An exploded schematic diagram of an embodiment of a battery pack is shown;
[0080] Fig.10 is a schematic diagram of an embodiment of an electric device including the secondary battery of the present application as a power source;
[0081] In the drawings, the drawings may not be drawn according to the actual scale. The reference numerals are explained as follows: 1 battery pack, 2 upper box, 3 lower box, 4 battery module, 5 secondary battery, 51 housing, 52 electrode assembly, 53 cover plate. DETAILED DESCRIPTION
[0082] Below, the embodiments of the current collector, pole piece, secondary battery, electric device, copper foil and the method for preparing the copper foil of the present application are specifically disclosed with appropriate reference to the accompanying drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0083] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0084] If not otherwise specified, all embodiments and optional embodiments of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.
[0085] Unless otherwise specified, all technical features and optional technical features of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.
[0086] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0087] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0088] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0089] If not specifically stated, the terms used in this application have the commonly known meanings generally understood by those skilled in the art.
[0090] If not otherwise specified, the values of the parameters mentioned in this application can be measured using various test methods commonly used in the art, for example, they can be measured according to the test methods given in this application.
[0091] If not otherwise specified, in the present application, the term "active ions" refers to ions that can be intercalated and extracted back and forth between the positive electrode and the negative electrode of a secondary battery, including but not limited to lithium ions.
[0092] In the present application, the terms "plurality" and "multiple" refer to two or more.
[0093] With the increase in the energy density of secondary batteries, there is a demand for thinner and lighter current collectors for pole pieces. As the current collector becomes thinner, the maximum load that the current collector can bear decays sharply, and the thickness of the current collector that can be used for plastic deformation is severely reduced, resulting in a significant decrease in the tensile strength and elongation at break of the current collector, making it difficult for current collectors with conventional strength in the prior art to meet the use needs of secondary batteries. After thinning, ordinary strength current collectors are prone to fatigue fracture in the later stages of secondary battery cycles, which in turn leads to thermal runaway of the battery cell and safety accidents. Therefore, it is necessary to effectively improve the tensile strength and plasticity (elongation at break) of the current collector while making it thinner and lighter.
[0094] In the prior art, metal strengthening technology mostly uses ordinary incoherent grain boundaries or phase boundaries to hinder dislocation movement to improve strength. When a large number of incoherent grain boundaries are introduced into the material, the strength is significantly improved, but as the number of "obstacles" to dislocation movement continues to increase, the movement of lattice dislocations is severely hindered or even completely suppressed and cannot coordinate plastic deformation, so the material becomes brittle. This makes the strengthening of the mechanical properties of metal materials often at the expense of plasticity, and the strength of materials with excellent plasticity is often very low.
[0095] Based on this, the present application provides a current collector, which includes copper foil, wherein the average particle size of the grains in the copper foil is 50nm-400nm, and based on the total number of grains in the copper foil, the number of nanotwin grains accounts for greater than or equal to 60%.
[0096] In this article, the term "twin" refers to two crystals (or two parts of a crystal) that form a mirror-symmetrical orientation relationship along a common crystal plane (i.e. a specific orientation relationship). These two crystals are called "twins" and this common crystal plane is called the twin plane. Nanotwins refer to twins with a size of less than 1000 nanometers in all dimensions.
[0097] The average particle size of the grains in the copper foil can be tested by methods known in the art. As an example, the cross section of the copper foil is measured by a cross-sectional electron backscatter diffractometer (EBSD) and a scanning electron microscope to obtain an inverse pole figure distribution diagram, and the particle size of the grains in the cross section is counted to make a quantity distribution diagram, such as Figure 1 As shown, the skewed distribution is used for fitting, and the length corresponding to the peak value is taken as the average grain size of the grains. Among them, the average diameter of the equivalent circle of the grains is taken as the grain size.
[0098] In some embodiments, the average grain size of the copper foil may be 50 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, or any range therebetween.
[0099] In the present application, the proportion of the number of nanotwins can be tested by methods known in the art. As an example, electron backscatter diffraction (EBSD) combined with scanning electron microscopy is used to observe the cross section of the copper foil to obtain an inverse pole figure distribution map, in which different colors represent different grain orientations. Figure 2 For example, the red lines inside the grains are twin boundaries, indicating that they have twin structures. The size and number of twins can be counted through the analysis software of the electron backscatter diffractometer, and then the proportion of nano twin grains can be calculated. As an example, the grain characteristics are analyzed using the Oxford C-Nano+ electron backscatter diffractometer and its supporting software.
[0100] In some embodiments, based on the total number of grains in the copper foil, the proportion of the number of nanotwin grains can be selected to be 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 100% or any numerical range therebetween.
[0101] Twin structure is an effective means to improve the strength and plasticity of metals. The twin boundary is a coherent interface with neatly arranged atoms, which can maintain the mobility of dislocations while increasing the strength of the material by increasing the resistance to dislocation movement, thereby maintaining the plasticity of the material while strengthening the material. However, copper foils strengthened by twin strengthening in the prior art often introduce micron-level twins during the preparation process, which hinders the further improvement of the strength of the copper foil. The copper foil provided in the embodiment of the present application has a high proportion of nano twins, which significantly improves the strength of the copper foil while improving the plasticity of the copper foil. The small grain size can further increase the interface structure, increase the external stress required for dislocations to pass through the grain boundary, and achieve material strengthening. The high proportion of nano twin structure and small grain size work together to help improve the mechanical strength of the copper foil while maintaining its high plasticity, providing a material basis for further improvement of battery energy density and safety.
[0102] In some embodiments, the average grain size of the copper foil is 50 nm to 300 nm.
[0103] Copper foil with an average particle size within the above range can further improve its mechanical strength while maintaining its high plasticity, meeting the use requirements of a new generation of high energy density secondary batteries.
[0104] In some embodiments, based on the total number of grains in the copper foil, the number of grains with a particle size less than 200 nm accounts for 20%-40%, and the number of grains with a particle size between 200 nm and 500 nm accounts for 50%-80%.
[0105] In some embodiments, based on the total number of grains in the copper foil, the percentage of grains with a grain size less than 200 nm may be 20%, 24%, 28%, 32%, 36%, 40% or any range therebetween.
[0106] In some embodiments, based on the total number of grains in the copper foil, the number of grains with a particle size between 200 nm and 500 nm may be 50%, 55%, 60%, 65%, 70%, 75%, 80% or any range therebetween.
[0107] In some implementations, based on the total number of crystal grains in the copper foil, the number of crystal grains with a particle size greater than 500 nm accounts for less than or equal to 5%, and may be less than or equal to 2%.
[0108] In some embodiments, based on the total number of grains in the copper foil, the percentage of grains with a particle size greater than 500 nm may be 0.5%, 1%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% or any range therebetween.
[0109] The copper foil grains provided in the embodiment of the present application have a small average particle size, a skewed particle size distribution, and a very small proportion of grains with a particle size greater than 500 nm. The fine grains reduce the occurrence of concentrated stress during the deformation of the copper foil and are more conducive to the coordinated sliding of the grains. Therefore, the strength of the copper foil can be improved while the elongation at break can be improved.
[0110] In some embodiments, based on the total number of grains in the copper foil, the proportion of equiaxed grains or quasi-equiaxed grains is greater than or equal to 80%, and can be optionally greater than or equal to 90%, and the ratio a1 of the major axis to the minor axis length of the equiaxed grains or quasi-equiaxed grains satisfies: 1≤a1<2.
[0111] Herein, the term "equiaxed grains or quasi-equiaxed grains" refers to grains whose major axis and minor axis are equal or have a small difference. In some embodiments, the major axis to minor axis length ratio a1 of the equiaxed grains or quasi-equiaxed grains satisfies: 1≤a1<2.
[0112] In the present application, the percentage of the number of equiaxed grains or quasi-equiaxed grains can be tested by methods known in the art. As an example, electron backscatter diffraction (EBSD) combined with a scanning electron microscope is used to observe the cross-section of the copper foil to obtain an inverse pole figure distribution diagram, and the percentage of the number of equiaxed grains or quasi-equiaxed grains is statistically analyzed by analysis software.
[0113] A large number of equiaxed grains or quasi-equiaxed grains are conducive to achieving fine and uniform grains in the copper foil, and the equiaxed grains or quasi-equiaxed grains have the same or similar properties in all directions, which is conducive to comprehensively improving the strength and plasticity of the copper foil.
[0114] In some embodiments, based on the total number of grains in the copper foil, the number of equiaxed grains or quasi-equiaxed grains accounts for 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 100% or any range therebetween.
[0115] In some embodiments, based on the total number of grains in the copper foil, the number of columnar grains accounts for less than 10%, and the ratio a2 of the length of the major axis to the minor axis of the columnar grains satisfies: a2>2.
[0116] The formation of columnar grains can easily lead to the heterogeneity of the mechanical properties of copper foil. Reducing the proportion of columnar grains is beneficial to improving the mechanical strength and plasticity of copper foil and reducing the probability of forming stress concentration points.
[0117] In some embodiments, the long axis direction of the columnar grains is the thickness direction of the copper foil.
[0118] In some embodiments, the crystal plane diffraction intensity of the (111) texture in the copper foil accounts for a ratio greater than or equal to 60% of the total crystal plane diffraction intensity of the (111) texture, (200) texture, (220) texture, (311) texture, and (222) texture in the copper foil, and can be optionally 60%-85%.
[0119] In this article, the term "texture" refers to the phenomenon that during the formation of the crystal, the grains in the polycrystal are arranged in an orderly manner along certain directions, showing a more or less statistically uneven distribution, that is, they appear to be clustered and arranged in certain directions, so the probability of orientation in these directions is significantly increased, which is also called preferred orientation or preferential orientation.
[0120] In the present application, the crystal plane diffraction intensity of the texture in the copper foil can be tested by a method known in the art. As an example, the copper foil is tested by an X-ray diffractometer, and the X-ray spectrum of the standard copper powder (PDF No.04-0836) is referred to. The peak area of the diffraction peak with a peak position of 40°-45° is taken as the crystal plane diffraction intensity of the (111) texture, the peak area of the diffraction peak with a peak position of 47°-52° is taken as the crystal plane diffraction intensity of the (200) texture, the peak area of the diffraction peak with a peak position of 70°-75° is taken as the crystal plane diffraction intensity of the (220) texture, the peak area of the diffraction peak with a peak position of 85°-95° is taken as the crystal plane diffraction intensity of the (311) texture, and the peak area of the diffraction peak with a peak position of 103°-107° is taken as the crystal plane diffraction intensity of the (222) texture.
[0121] In some embodiments, the ratio of the crystal plane diffraction intensity of the (111) texture in the copper foil to the total crystal plane diffraction intensity of the (111) texture, (200) texture, (220) texture, (311) texture, and (222) texture in the copper foil can be selected to be 60%, 65%, 70%, 75%, 80%, 85% or any numerical range therebetween.
[0122] For pure copper materials, common textures include (111), (200), (220), (311), and (222). According to crystallographic properties, the (111) crystal plane has a high atomic density and high mechanical strength, which can improve the twin strengthening effect. A high proportion of (111) texture in copper foil is beneficial to improving the mechanical strengthening and plastic strengthening effects of copper foil.
[0123] In some embodiments, the copper foil has a first surface and a second surface relative to each other, the thickness of the copper foil is denoted as H, the area from the first surface of the copper foil to the thickness range of 0.2H-0.5H is denoted as the first area of the copper foil, and the area from the second surface of the copper foil to the thickness range of 0.2H-0.5H is denoted as the second area of the copper foil, and the absolute value of the difference between the average particle size of the grains in the first area and the average particle size of the grains in the second area is less than or equal to 150nm.
[0124] In some embodiments, the absolute value of the difference between the average grain size of the grains in the first region and the average grain size of the grains in the second region is 1 nm, 20 nm, 40 nm, 60 nm, 80 nm, 100 nm, 120 nm, 140 nm, 150 nm or any numerical range therebetween.
[0125] The grain size and structure of the copper foil are also highly uniform along the thickness direction of the copper foil, indicating that uniform deposition is achieved in different deposition time periods and the electrolyte does not undergo obvious polarization during the deposition process, providing a basis for it to maintain high strength and high plasticity while having an ultra-thin thickness.
[0126] In some embodiments, based on the total number of grains in the copper foil, the number of nanotwin grains accounts for 65% to 90%.
[0127] In some embodiments, the maximum surface roughness of the copper foil is less than or equal to 3 μm.
[0128] The maximum surface roughness of the copper foil can reflect the uniformity and smoothness of the copper foil surface. The maximum surface roughness of the copper foil can be tested by methods known in the art, for example, using a stylus roughness tester to test, wiping the surface of the copper foil with alcohol, placing the copper foil steadily on a horizontal surface, placing the stylus roughness tester on the surface of the copper foil, making the probe contact the surface of the copper foil, and gently swiping the probe along its surface, and obtaining the roughness of the copper foil through the instrument reading. Test five times at different parts of the copper foil, and take the maximum value of the reading as the maximum surface roughness of the copper foil.
[0129] In some embodiments, the maximum surface roughness of the copper foil may be 0.1 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, or any range therebetween.
[0130] Copper foil with a maximum surface roughness of less than or equal to 3μm has a smooth and uniform surface, and is not easy to form stress concentration points during cyclic stress, which is beneficial to improving the mechanical strength and plasticity of the copper foil.
[0131] In some embodiments, the thickness H of the copper foil satisfies: 3 μm≤H≤15 μm, and may be 3 μm≤H≤8 μm.
[0132] In some embodiments, the thickness H of the copper foil may be 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, or any range therebetween.
[0133] In this application, the thickness of the copper foil can be tested by a method known in the art. As an example, a 20×15 cm 2 The cut sample is placed on an electronic balance for weighing to obtain the sample weight. Then, according to the density of copper foil, ρ is 8.96 g / cm 3 Calculate the volume of the spline. Given the length and width of the spline, the thickness of the spline can be calculated.
[0134] The copper foil has a low thickness, which can effectively reduce the weight of the battery and is conducive to further improving the energy density of the battery.
[0135] In some embodiments, under the test conditions of room temperature, sample thickness of 6±0.2 μm, and stretching speed of 50±0.5 mm / min, the tensile strength of the copper foil is greater than or equal to 600 MPa and the elongation at break of the copper foil is greater than or equal to 4%; optionally, the tensile strength of the copper foil is 700 MPa-1500 MPa, and can be further optionally 800 MPa-1000 MPa; the elongation at break of the copper foil is 4.5%-10%, and can be further optionally 5%-8%.
[0136] Herein, the term "room temperature" refers to 20±10°C.
[0137] As used herein, the term "tensile strength" refers to the maximum bearing strength of a specimen when continuous loading is applied to the specimen until it breaks.
[0138] In this article, the term "elongation at break" refers to the ratio of the length change of a material when it undergoes plastic deformation until it breaks after being subjected to force to its original length. It is usually expressed as a percentage and is an important parameter for measuring the deformation ability of a material under stress during stretching.
[0139] In the present application, the tensile strength and elongation at break of the copper foil can be tested by methods known in the art, such as testing according to GB / T 5230-1995 "Electrolytic Copper Foil" standard. As an example, cut at least 4 samples with a length of 200±0.5mm, a width of 15±0.25mm, and a thickness of 6±0.2μm, and continuously apply load to the samples at a tensile speed of 50±0.5mm / min at room temperature until they break. The maximum load divided by the cross-sectional area of the sample is taken as the tensile strength of the sample. The cross-sectional area of the sample can be calculated by dividing the mass of the sample by the product of the length and density of the sample. The density of the copper foil sample can be taken as 8.9g / cm 3 .
[0140] In some embodiments, under the test conditions of room temperature, sample thickness of 6um±0.2μm, and stretching speed of 50±0.5mm / min, the tensile strength of the copper foil can be selected as 600MPa, 700MPa, 800MPa, 900MPa, 1000MPa, 1100MPa, 1200MPa, 1300MPa, 1400MPa, 1500MPa or any range therebetween; the elongation at break of the copper foil can be selected as 4%, 4.5%, 5%, 6%, 7%, 8%, 9%, 10% or any range therebetween.
[0141] The copper foil has both high strength and high plasticity, which can meet the use requirements of high energy density batteries, improving the safety of the battery while increasing the energy density of the battery.
[0142] The present application also provides a method for preparing copper foil, which is prepared by electroplating. The electroplating method specifically includes periodically applying current to an electrolyte to reduce and deposit copper ions in the electrolyte to form copper foil. The average particle size of grains in the copper foil is 50nm-400nm, and based on the total number of grains in the copper foil, the number of nanotwin grains accounts for greater than or equal to 60%, optionally, greater than or equal to 65%.
[0143] In this article, the term "electroplating" refers to a method of depositing metal or alloy on the surface of a workpiece to form a metal layer by using the principle of electrolysis.
[0144] In some embodiments, the current is a pulse current, and the pulse current includes one or more of a square wave pulse current, a sine wave pulse current, a triangle wave pulse current, and a sawtooth wave pulse current.
[0145] In some embodiments, the pulsed current comprises a square wave pulsed current.
[0146] As used herein, the term "pulsed current" refers to current or voltage pulses that occur repeatedly in a cycle.
[0147] Applying pulse current to the electrolyte can control the process of nucleation and grain growth of reduced copper ions by turning the current on and off, thereby inhibiting grain growth and forming uniform nano-grains to improve the tensile strength and elongation at break of the copper foil. Compared with the DC current deposition commonly used in the prior art, pulse current deposition can achieve a higher peak current density, which is conducive to the nucleation of a large number of copper foils to increase the density of the copper foil and reduce the grain size of the copper foil to improve the mechanical strength of the copper foil.
[0148] In some embodiments, the electrolyte includes copper ions and chloride ions.
[0149] In some embodiments, the concentration of copper ions in the electrolyte is 30 g / L-100 g / L, optionally 45 g / L-75 g / L.
[0150] In some embodiments, the concentration of copper ions in the electrolyte is 30 g / L, 40 g / L, 50 g / L, 60 g / L, 70 g / L, 80 g / L, 90 g / L, 100 g / L, or any range therebetween.
[0151] The research results show that the combination of low copper ion concentration and high additive concentration is more conducive to comprehensively improving the strength and elongation at break of copper foil than the combination of high copper ion concentration and low additive concentration. In addition, low copper ion concentration helps to control the growth and deposition rate of grains, which is conducive to the preparation of small-sized grains and improves the mechanical strength of copper foil.
[0152] In some embodiments, the concentration of chloride ions is 10 mg / L-80 mg / L.
[0153] In some embodiments, the concentration of chloride ions is 10 mg / L, 20 mg / L, 30 mg / L, 40 mg / L, 50 mg / L, 60 mg / L, 70 mg / L, 80 mg / L, or any range therebetween.
[0154] In some embodiments, the electrolyte further includes an additive, wherein the additive includes one or more of a leveling agent, a wetting agent, and a brightener.
[0155] As used herein, the term "leveler" refers to a substance added to the electrolyte to improve the flatness of the plated layer.
[0156] In this article, the term "wetting agent" refers to a substance used to reduce the interfacial tension between the electrolyte / electrode and to achieve better adhesion of the coating to the substrate.
[0157] In this article, the term "brightener" refers to a substance that improves the smoothness of the coating and reduces the surface roughness.
[0158] The leveling agent can adhere to the tip of the aluminum foil with a fast deposition rate, inhibit the growth of grains, balance the growth rate of pits and tips, and improve the flatness of the aluminum foil. The wetting agent can improve the wettability of the electrolyte and the substrate. The wettability of the electrolyte on the cathode is sufficient to achieve rapid electrodeposition with a large current, increase the nucleation rate of the copper foil, and reduce the average particle size of the grains in the copper foil. The brightener can make the grain size of the copper foil smaller, reduce the surface roughness of the copper foil, and improve the smoothness of the surface.
[0159] In some embodiments, the additives include a leveler, a wetting agent, and a brightener.
[0160] The research results show that adding multiple additives at the same time can produce a synergistic effect and effectively improve the strength and plasticity of copper foil.
[0161] In some embodiments, the leveling agent includes one or more of gelatin and Janus Green; the wetting agent includes one or more of hydroxyethyl cellulose and polyethylene glycol; the brightening agent includes one or more of sodium polydisulfide propane sulfonate, sodium 3-mercapto-1-propane sulfonate, and thiourea.
[0162] In some embodiments, the wetting agent includes hydroxyethylcellulose and polyethylene glycol.
[0163] The results show that adding two different wetting agents at the same time can more effectively improve the mechanical strength of copper foil than adding a single type of wetting agent. Although the mechanism is not clear, it is speculated that it may be related to the competitive adsorption of two different types of additives, which is beneficial to improve the consistency of grains during the deposition process, reduce the difference in grain size in the thickness direction, and improve the uniformity of copper foil.
[0164] In some embodiments, the concentration of the leveler in the electrolyte is 20 mg / L-300 mg / L, and can be 50 mg / L-150 mg / L.
[0165] In some embodiments, the concentration of the leveler in the electrolyte is 20 mg / L, 50 mg / L, 100 mg / L, 150 mg / L, 200 mg / L, 250 g / L, 300 mg / L, or any range therebetween.
[0166] In some embodiments, the concentration of the wetting agent in the electrolyte is 10 mg / L-200 mg / L, and can be optionally 30 mg / L-100 mg / L.
[0167] In some embodiments, the concentration of the wetting agent in the electrolyte is 10 mg / L, 30 mg / L, 50 mg / L, 80 mg / L, 100 mg / L, 130 mg / L, 150 mg / L, 180 mg / L, 200 mg / L, or any range therebetween.
[0168] In some embodiments, the concentration of the brightener in the electrolyte is 10 mg / L-200 mg / L.
[0169] In some embodiments, the concentration of the brightener in the electrolyte is 10 mg / L, 20 mg / L, 30 mg / L, 40 mg / L, 50 mg / L, 60 mg / L, 70 mg / L, 80 mg / L, 90 mg / L, 100 mg / L, 110 mg / L, 120 mg / L, 130 mg / L, 140 mg / L, 150 mg / L, 160 mg / L, 170 mg / L, 180 mg / L, 190 mg / L, 200 mg / L or any range therebetween.
[0170] In some embodiments, the pH of the electrolyte is 2.5-4.4.
[0171] In some embodiments, the pH of the electrolyte is 2.5, 2.7, 2.9, 3.1, 3.3, 3.5, 3.7, 3.9, 4.1, 4.4, or any range therebetween.
[0172] In some embodiments, the mass concentration ratio of the copper ion to the leveler is 500:1-4500:1; and / or the mass concentration ratio of the copper ion to the brightener is 300:1-6000:1.
[0173] In some embodiments, the mass concentration ratio of the copper ion to the leveler can be 500:1, 1000:1, 1500:1, 2000:1, 2500:1, 3000:1, 3500:1, 4000:1, 4500:1 or any range therebetween.
[0174] In some embodiments, the mass concentration ratio of the copper ion to the brightener can be selected as 300:1, 1000:1, 2000:1, 3000:1, 4000:1, 5000:1, 6000:1 or any numerical range therebetween.
[0175] In some embodiments, the electrolyte includes gelatin at a concentration of 20 mg / L-150 mg / L, polyethylene glycol at a concentration of 15 mg / L-100 mg / L, hydroxyethyl cellulose at a concentration of 10 mg / L-80 mg / L, sodium polydisulfide dipropane sulfonate at a concentration of 15 mg / L-150 mg / L, copper ions at a concentration of 45 g / L-90 g / L, and chloride ions at a concentration of 10 mg / L-80 mg / L.
[0176] In some embodiments, the peak current density of the pulse current is I, in A / dm 2 The current duty cycle of the pulse current is s, and the peak current density I and the duty cycle s satisfy: 2A / dm 2 ≤I×s≤18A / dm 2 .
[0177] In this document, the term “current duty cycle of a pulse current” refers to the proportion of the current conduction time in the pulse current to the entire pulse period.
[0178] In some embodiments, the product of the peak current density I and the duty cycle s is 2A / dm 2 , 4A / dm 2 、6A / dm 2 , 8A / dm 2 、10A / dm 2 、12A / dm 2 、14A / dm 2 、16A / dm 2 、18A / dm 2 Or any range of values in between.
[0179] The product of the peak current density I and the duty cycle s is equivalent to the average density of the current in the pulse period. The pulse current deposition method allows the average density of the current in the pulse period to be higher than the maximum current density that can be achieved during DC deposition, because too high a DC deposition density will cause hydrogen evolution and concentration polarization in the electrolyte, reducing the uniformity of the copper foil during the electrodeposition process. The product of the peak current density I and the duty cycle s within the above range enables the dynamic balance of copper ion consumption and replenishment in the electrolyte to be achieved by controlling the opening and closing of the current, reducing the concentration difference between the copper ion deposition site and other parts of the electrolyte, so that the electrolyte will not undergo significant concentration polarization, and improving the uniformity of the grain size in the thickness direction of the prepared copper foil. Moreover, the product of the peak current density I and the duty cycle s within the above range can control the nucleation and growth rate of the grains, realize the preparation of small-size grains, and improve the mechanical strength of the copper foil.
[0180] In some embodiments, the peak current density I of the pulse current satisfies: 3.3A / dm 2 ≤I≤333A / dm 22 .
[0181] In some embodiments, the peak current density I of the pulse current is 3.3A / dm 2 、8.35A / dm 2 、10A / dm 2 、100A / dm 2 、150A / dm 2 、167A / dm 2 、180A / dm 2 、200A / dm 2 、300A / dm 2 、333A / dm 2 Or any range of values in between.
[0182] In some embodiments, the duty cycle s of the pulse current is 2% to 50%.
[0183] In some embodiments, the duty cycle s of the pulse current is 2%, 3.30%, 5%, 10%, 20%, 30%, 40%, 50% or any range therebetween.
[0184] In some embodiments, the pulse width of the pulse current is 1 ms to 50 ms.
[0185] In this article, the term "pulse width" refers to the duration of current within a pulse period.
[0186] In some embodiments, the pulse width of the pulse current is 1 ms, 5 ms, 10 ms, 15 ms, 20 ms, 25 ms, 30 ms, 35 ms, 40 ms, 45 ms, 50 ms, or any range therebetween.
[0187] In some embodiments, the distance between the cathode electrode and the anode electrode is 15 mm to 20 mm.
[0188] In some embodiments, the distance between the cathode electrode and the anode electrode is 15 mm, 16 mm, 17 mm, 18 mm, 19 mm, 20 mm, or any range therebetween.
[0189] In some embodiments, the deposition temperature is 45°C-60°C.
[0190] In some embodiments, the deposition temperature may be 45° C., 50° C., 55° C., 60° C., or any range therebetween.
[0191] In some embodiments, the cathode electrode is a titanium roller or plate.
[0192] In some embodiments, the anode electrode is a titanium substrate plate.
[0193] In some embodiments, the deposition time is greater than or equal to 80 s.
[0194] In some embodiments, the deposition time may be 80 s, 100 s, 200 s, 220 s, 240 s, 280 s, 300 s, 400 s, 500 s, 800 s, 1000 s, or any range therebetween.
[0195] In some embodiments, the electroplating method specifically includes periodically applying a pulse current to the electrolyte so that the copper ions in the electrolyte are reduced and deposited; wherein the peak current density I of the pulse current satisfies 100A / dm 2 ≤I≤180A / dm 2 The duty cycle s of the pulse current satisfies: 2%≤s≤10%, and the deposition time is 80s-250s.
[0196] In some embodiments, the preparation method is a continuous production method.
[0197] In some embodiments, the preparation method is a roller deposition method. Its working principle is that the cathode roller is connected to the negative electrode of the power supply, and the anode tank is connected to the positive electrode of the power supply. When the electrolyte containing copper ions enters the anode tank, an electric field is formed between the positive and negative electrodes. Under the action of the electric field, the copper ions migrate and deposit on the surface of the cathode roller, and the deposited copper foil is peeled off from the cathode roller and rolled on another roller. The electrolyte is continuously added and circulated, and the copper ions are continuously deposited on the cathode roller under the action of the electric field, continuously peeled off and rolled on the winding shaft. This preparation method can realize the continuous production of large-scale copper foil, providing the possibility for industrial application.
[0198] The present application also provides a copper foil, which includes the same features as the copper foil in the aforementioned current collector, which will not be repeated here.
[0199] In any embodiment, the copper foil is prepared by the preparation method in any embodiment above.
[0200] In some embodiments, the maximum width of the copper foil is greater than or equal to 1.5 meters, and / or the maximum length of the copper foil is greater than or equal to 10,000 meters.
[0201] In some embodiments, the maximum width of the copper foil is 1.5 meters, 2 meters, 2.5 meters, 3 meters, 3.5 meters, 4 meters, 6 meters, 8 meters, 10 meters, or any range therebetween.
[0202] In some embodiments, the maximum width of the copper foil is 10,000 meters, 15,000 meters, 20,000 meters, 25,000 meters, 30,000 meters, 60,000 meters, 100,000 meters, or any range therebetween.
[0203] The copper foil provided in the embodiment of the present application can be manufactured in large sizes and has the prospect of industrial application.
[0204] Pole piece
[0205] The present application also provides a pole piece, which includes a current collector in any embodiment.
[0206] In some embodiments, the electrode sheet is a negative electrode sheet, and the current collector is a negative electrode current collector.
[0207] In some embodiments, the negative electrode plate includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector. For example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0208] In some embodiments, the negative electrode film layer includes a negative electrode active material. In some embodiments, the negative electrode active material includes, but is not limited to, one or more of conventional natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based material may include one or more of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite, and silicon alloy material. The tin-based material may include one or more of elemental tin, tin oxide, and tin alloy material.
[0209] In some embodiments, the negative electrode film layer may further include a negative electrode conductive agent. The present application has no particular restrictions on the type of the negative electrode conductive agent. As an example, the negative electrode conductive agent may include one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0210] In some embodiments, the negative electrode film layer may further include a negative electrode binder. The present application has no particular restrictions on the type of the negative electrode binder. As an example, the negative electrode binder may include one or more of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS).
[0211] In some embodiments, the negative electrode film layer may further include other additives. As an example, the other additives may include a thickener, such as sodium carboxymethyl cellulose (CMC), a PTC thermistor material, and the like.
[0212] The negative electrode film layer is usually formed by coating the negative electrode slurry on the negative electrode current collector, drying and cold pressing. The negative electrode slurry is usually formed by dispersing the negative electrode active material, optional conductive agent, optional binder, and other optional auxiliary agents in a solvent and stirring them uniformly. The solvent can be N-methylpyrrolidone (NMP) or deionized water, but is not limited thereto.
[0213] The negative electrode plate does not exclude other additional functional layers in addition to the negative electrode film layer. For example, in some embodiments, the negative electrode plate described in the present application also includes a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode collector and the negative electrode film layer and disposed on the surface of the negative electrode collector; in some embodiments, the negative electrode plate described in the present application also includes a protective layer covering the surface of the negative electrode film layer.
[0214] Secondary battery
[0215] The present application also provides a secondary battery, which may be in the form of a battery cell, a battery module or a battery pack.
[0216] In some embodiments, the maximum expansion force of the secondary battery cell is greater than or equal to 1000 kgf.
[0217] In some embodiments, the maximum expansion force of the secondary battery cell is greater than or equal to 2500 kgf.
[0218] In some embodiments, the maximum expansion force of the secondary battery cell is greater than or equal to 4000 kgf.
[0219] 1kgf refers to the gravity of a 1-kilogram object at sea level at 45 degrees north latitude. 1kgf is approximately 9.8 Newtons. The expansion force of the secondary battery cell is sensed by a pressure sensor disposed in a fixture on both sides of the large surface of the secondary battery cell pole piece.
[0220] The current collector in the prior art is prone to breakage under the high expansion force of the secondary battery, causing safety accidents and limiting the further improvement of the electrochemical performance of the secondary battery. The current collector provided in the embodiment of the present application has excellent tensile strength and elongation at break, can be applied to secondary batteries with high expansion force, and is conducive to further improving the energy density of the secondary battery.
[0221] The present application has no particular restrictions on the type of secondary battery. For example, the secondary battery can be a lithium-ion battery, etc. In general, a secondary battery includes a positive electrode plate, a negative electrode plate, and an electrolyte, etc. During the charge and discharge process of the secondary battery, active ions are embedded and removed back and forth between the positive electrode plate and the negative electrode plate, and the electrolyte plays a role in conducting active ions between the positive electrode plate and the negative electrode plate. The present application has no particular restrictions on the type of the electrolyte, which can be selected according to actual needs. For example, the electrolyte can be selected from at least one of a solid electrolyte and a liquid electrolyte (ie, an electrolyte). Secondary batteries using electrolytes and some secondary batteries using solid electrolytes may also include a separator, which is arranged between the positive electrode plate and the negative electrode plate to play an isolation role.
[0222] [Positive electrode]
[0223] In some embodiments, the positive electrode plate includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector. For example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0224] The positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).
[0225] The positive electrode film layer generally comprises a positive electrode active material, an optional binder and an optional conductive agent. The positive electrode film layer is generally formed by coating the positive electrode slurry on the positive electrode current collector, drying and cold pressing. The positive electrode slurry is generally formed by dispersing the positive electrode active material, the optional conductive agent, the optional binder and any other components in a solvent and stirring evenly. The solvent may be N-methylpyrrolidone (NMP), but is not limited thereto. As an example, the binder for the positive electrode film layer may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin. As an example, the conductive agent for the positive electrode film layer includes one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0226] The positive electrode active material may be a positive electrode active material for a secondary battery known in the art.
[0227] When the secondary battery of the present application is a lithium-ion battery, the positive electrode active material may include, but is not limited to, one or more of lithium-containing transition metal oxides, lithium-containing phosphates, and their respective modified compounds. Examples of the lithium transition metal oxide may include, but are not limited to, one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their respective modified compounds. Examples of the lithium-containing phosphate may include, but are not limited to, one or more of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, a composite material of lithium iron manganese phosphate and carbon, and their respective modified compounds.
[0228] In some embodiments, in order to further improve the energy density of the secondary battery, the positive electrode active material for the lithium ion battery may include a general formula of Li a Ni b Coc M d O e A f One or more of lithium transition metal oxides and their modified compounds thereof. 0.8 ≤ a ≤ 1.2, 0.5 ≤ b < 1, 0 < c < 1, 0 < d < 1, 1 ≤ e ≤ 2, 0 ≤ f ≤ 1, M is selected from one or more of Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, and B, and A is selected from one or more of N, F, S, and Cl.
[0229] In some embodiments, by way of example, the positive electrode active material for a lithium-ion battery may include one or more of LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2 (NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2 (NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), LiNi 0.85 Co 0.15 Al 0.05 O2, LiFePO4, and LiMnPO4.
[0230] In the present application, the modified compounds of the above positive electrode active materials may be doping modification and / or surface coating modification of the positive electrode active materials.
[0231] [Electrolyte]
[0232] In some embodiments, the electrolyte uses an electrolytic solution, and the electrolytic solution includes an electrolyte salt and a solvent.
[0233] The type of the electrolyte salt is not specifically limited and can be selected according to actual needs.
[0234] When the secondary battery of the present application is a lithium ion battery, as an example, the electrolyte salt may include one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0235] The type of the solvent is not specifically limited and can be selected according to actual needs. In some embodiments, as an example, the solvent may include ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS) and diethyl sulfone (ESE) One or more.
[0236] In some embodiments, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain properties of the secondary battery, such as additives that improve the overcharge performance of the secondary battery, additives that improve the high temperature performance of the secondary battery, and additives that improve the low temperature power performance of the secondary battery.
[0237] [Isolation film]
[0238] The present application has no particular limitation on the type of the isolation membrane, and any known porous structure isolation membrane with good chemical stability and mechanical stability can be selected.
[0239] In some embodiments, the material of the isolation membrane may include one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film. When the isolation membrane is a multi-layer composite film, the materials of each layer are the same or different.
[0240] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet can be formed into an electrode assembly by a winding process or a lamination process.
[0241] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0242] In some embodiments, the outer packaging can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT) and polybutylene succinate (PBS).
[0243] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 5 The secondary battery 5 is a square structure as an example.
[0244] In some embodiments, Figure 6 As shown, the outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation film can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, which can be adjusted according to demand.
[0245] The preparation method of the secondary battery of the present application is well known. In some embodiments, the positive electrode sheet, the separator, the negative electrode sheet and the electrolyte can be assembled to form a secondary battery. As an example, the positive electrode sheet, the separator and the negative electrode sheet can be formed into an electrode assembly through a winding process or a lamination process, and the electrode assembly is placed in an outer package, and the electrolyte is injected after drying, and the secondary battery is obtained through vacuum packaging, standing, forming, shaping and other processes.
[0246] In some embodiments of the present application, the secondary batteries according to the present application can be assembled into a battery module. The battery module can contain multiple secondary batteries, and the specific number can be adjusted according to the application and capacity of the battery module.
[0247] Figure 7 FIG. 4 is a schematic diagram of a battery module 4 as an example. Figure 7 As shown, in the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.
[0248] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0249] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0250] Figure 8 and Fig. 9 FIG. 1 is a schematic diagram of a battery pack 1 as an example. Figure 8 and Fig. 9 As shown, the battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3, wherein the upper box body 2 is used to cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.
[0251] Electrical devices
[0252] The present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack of the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device can be, but is not limited to, a mobile device (such as a mobile phone, a tablet computer, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.
[0253] The electrical device may select a secondary battery, a battery module or a battery pack according to its usage requirements.
[0254] Fig.10 Schematic diagram of an electric device as an example. The electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the requirements of the electric device for high power and high energy density, a battery pack or a battery module may be used.
[0255] As another example, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. The electric device is usually required to be light and thin, and a secondary battery may be used as a power source.
[0256] Example
[0257] The following examples describe the disclosure of the present application in more detail, and these examples are only for illustrative purposes, as it is obvious to those skilled in the art that various modifications and variations are made within the scope of the disclosure of the present application. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are based on mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.
[0258] Example 1
[0259] (1) Preparation of copper foil
[0260] A copper plate or copper wire with a purity of more than 99.9% is dissolved in a sulfuric acid solution to prepare a copper sulfate pentahydrate solution, which is used as a copper source, and an electrolyte is prepared at 60°C with additives and oxalic acid, wherein the additives include gelatin, polyethylene glycol, hydroxyethyl cellulose and sodium chloride. The pH of the electrolyte is 3.5, and the concentrations of the components are as follows: copper ion concentration is 45g / L; gelatin concentration is 90mg / L; polyethylene glycol concentration is 50mg / L; hydroxyethyl cellulose concentration is 30mg / L; chloride ion concentration is 80mg / L, sodium polydisulfide dipropane sulfonate concentration is 75mg / L, and the rest is deionized water.
[0261] A square wave pulse current waveform is used to periodically apply current to the polished cathode titanium roller. The area of the titanium roller in the electrolyte is 0.3dm 2 The rotation speed of the titanium roller is 2m / min, and a pulse current is applied with a current density of 167A / dm 2 , duty cycle 5%, pulse width 1ms, cathode-anode distance 20mm, deposition temperature 60°C. Electroplating time 224s, copper foil deposited on titanium roller.
[0262] (2) Preparation of batteries
[0263] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive agent acetylene black, and binder polyvinylidene fluoride (PVDF) are dissolved in solvent N-methylpyrrolidone (NMP) in a weight ratio of 90:5:5, and the positive electrode slurry is obtained after being fully stirred and mixed. Thereafter, the positive electrode slurry is evenly coated on the positive electrode collector, and then dried, cold pressed, and cut to obtain the positive electrode sheet.
[0264] The negative electrode active material artificial graphite, the conductive agent acetylene black, the binder styrene butadiene rubber (SBR), and the thickener sodium carboxymethyl cellulose (CMC) are dissolved in the solvent deionized water in a weight ratio of 90:4:4:2, and are evenly mixed to prepare a negative electrode slurry; then the negative electrode slurry is evenly coated on the negative electrode collector copper foil once or multiple times, and a negative electrode film is obtained after drying, and then a negative electrode sheet is obtained by cold pressing and slitting.
[0265] In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), the organic solvents fluoroethylene carbonate (FEC), ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed uniformly in a mass ratio of 1:2:7, and 12.5wt% LiPF6 lithium salt was added to dissolve in the organic solvent. Then, 2.0wt% of the compound represented by formula I-1, 0.5wt% of 1,3-propane sultone and 0.5wt% of succinic anhydride were added to the above organic solvent as additives, mixed and stirred uniformly, and an electrolyte was obtained.
[0266] Polypropylene film is used as the isolation film.
[0267] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is placed between the positive and negative electrode sheets to play an isolating role, and then they are wound to obtain an electrode assembly; the electrode assembly is placed in a battery casing, and after drying, the electrolyte is injected, and then a lithium-ion battery is obtained through processes such as formation and standing.
[0268] Embodiment 2-8
[0269] The preparation methods of Examples 2-8 are basically the same as those of Example 1, except that the components or concentrations of the electrolyte or the parameters of the pulse deposition are changed, as shown in Table 1.
[0270] Comparative Example 1
[0271] The preparation method of comparative example 1 is basically the same as that of example 1, except that the electrodeposition method is changed to use direct current for deposition, and the deposition current density is 8.35 A / dm 2 , as shown in Table 1.
[0272] Table 1
[0273]
[0274] Performance Testing
[0275] (1) Thickness test
[0276] Take 20×15cm 2The thickness of the sample is calculated by weighing method, as follows: the cut sample is placed on an electronic balance to weigh the sample weight, and then the density of the copper foil is ρ 8.96g / cm 3 Calculate the volume of the spline. Given the length and width of the spline, the thickness of the spline can be calculated.
[0277] (2) Mechanical properties test
[0278] According to GB / T 5230-1995 "Electrolytic Copper Foil", cut into tensile specimens with a length L0 of 200 mm and a width of 15 mm, put the specimen on a balance and weigh it, and record the mass as m. Use a universal testing machine to test the tensile properties at 25°C, and set the tensile rate to 50 mm / min.
[0279] The cross-sectional area of the stretched spline is Where ρ is 8.96 g / cm 3 , m is in grams, and L0 is in centimeters.
[0280] Continuously apply load to the sample until it breaks, read the maximum load F from the force gauge or tensile curve, and calculate the tensile strength σ according to formula I b .
[0281]
[0282] The distance between the two lines after the sample is broken is L1, which can be measured on the sample or read from the tensile curve. L1 can be measured by the straight line method or the displacement method, and the elongation at break δ can be calculated according to formula II.
[0283]
[0284] (3) Grain characteristic test of copper foil
[0285] Electron backscatter diffraction (EBSD) combined with scanning electron microscopy was used to observe the cross section of the copper foil, where the electron backscatter diffractometer model was Oxford C-Nano+. The polar figure distribution map was obtained, and the particle size of each grain was measured. The diameter of the equivalent circle of the grain was used as the particle size of the grain, and the distribution statistics of the grain size were performed. The skewed distribution was used for fitting, and the particle size corresponding to the peak value was used as the average particle size of the grains in the copper foil. The number of twins was counted by the inverse pole figure, and different colors represent different grain orientations. The red lines inside the grains are twin boundaries, indicating that they have twin structures. The analysis software supporting the Oxford C-Nano+ electron backscatter diffractometer was used to count the number of nanotwins. A similar method was used to measure the number of equiaxed grains or quasi-equiaxed grains.
[0286] (4) Maximum surface roughness test
[0287] Wipe the copper foil surface with alcohol, place the copper foil on a flat surface, place the stylus roughness tester on the copper foil surface, make the stylus contact the copper foil surface, and gently run the stylus along the surface to get the roughness of the copper foil through the instrument reading. Test five times at different parts of the copper foil, and take the maximum value of the reading as the maximum roughness of the copper foil surface.
[0288] (5) State of Health (SOH) corresponding to crack failure
[0289] At 25°C, the battery is charged at a constant current of 1C to a voltage of 3.8V, then charged at a constant voltage of 3.8V to a current ≤0.05C, and then discharged at a constant current of 1C to a voltage of 2.5V. This is a charge and discharge process, and the charge and discharge cycle is repeated in this way. Then, electronic computer tomography (CT) is used to determine whether cracks occur inside the battery. If cracks occur, the battery that fails due to cracks during the cycle is disassembled, the negative electrode of the battery is disassembled, and samples are taken at the place where no cracks appear. The elongation at break of the sample is measured according to the measurement method of the elongation at break described above, and the SOH value of the battery at this time is obtained by simulation calculation.
[0290] Test Results
[0291] Table 2
[0292]
[0293]
[0294] Table 3
[0295] The test results of the embodiments and comparative examples are shown in Tables 1-3.
[0296] From the comparison between the embodiments and the comparative examples, it can be seen that the average particle size of the grains in the copper foil provided in the present application is 50nm-400nm, and based on the total number of grains in the copper foil, the number of twin grains accounts for not less than 60%, which has excellent tensile strength and elongation at break, can reduce the charge (SOH) value corresponding to battery crack failure, and help improve the safety and cycle life of the battery.
[0297] Figure 1 is a schematic diagram of the grain size distribution of the copper foil of Example 1; Figure 2 is an inverse pole figure distribution diagram of the electron backscatter diffraction image of the copper foil of Example 1; Figure 3 This is a tensile curve of the copper foil of Example 1. Figure 1 and Figure 2It can be seen that the average particle size of the grains in the copper foil of Example 1 is 200nm; the minimum particle size of the grains is about 10nm; based on the total number of grains in the copper foil, the number of grains with a particle size below 200nm accounts for 34%, the number of grains with a particle size of 200-500nm accounts for about 65%, and the number of grains with a particle size greater than 500nm accounts for no more than 2%; the maximum roughness of the copper foil surface is 0.12um. Figure 4 a is the X-ray diffraction pattern of the copper foil of Example 2; the crystal plane diffraction intensity of the (111) texture in the copper foil is 80.06% of the total crystal plane diffraction intensity of the (111) texture, (200) texture, (220) texture, (311) texture, and (222) texture in the copper foil. Figure 4 b For the copper foil in comparative example 1, the proportion of the crystal plane diffraction intensity of the (111) texture in the copper foil in the total crystal plane diffraction intensity of the (111) texture, (200) texture, (220) texture, (311) texture, and (222) texture in the copper foil is significantly increased.
[0298] It can be seen from Table 3 that when the additives in the electrolyte simultaneously contain a certain amount of leveling agent, wetting agent, and brightener, the maximum roughness of the copper foil surface can be reduced, and the tensile strength and elongation at break of the copper foil can be further improved simultaneously.
[0299] From the comparison of Examples 1, 2, and 8, it can be seen that, compared with the electrolyte containing high concentration of copper ions and low concentration of additives, the electrolyte containing low concentration of copper ions and high concentration of additives can further improve the tensile strength and elongation at break of the copper foil.
[0300] From the comparison between Examples 1, 4, 6 and Example 5, it can be seen that the high peak current density and duty cycle product increases the average grain size of the copper foil and decreases the mechanical properties, but is still better than Comparative Example 1.
[0301] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A current collector, characterized in that: The current collector includes copper foil, the average grain size of the grains in the copper foil is 50nm-400nm, and based on the total number of grains in the copper foil, the number of nano twin grains accounts for greater than or equal to 60%.
2. The current collector according to claim 1, characterized in that: The grains in the copper foil meet one or more of the following characteristics: (1) The average grain size of the copper foil is 50nm-300nm; (2) Based on the total number of grains in the copper foil, the number of grains with a grain size of less than 200 nm accounts for 20%-40%, and the number of grains with a grain size between 200 nm and 500 nm accounts for 50%-80%; (3) Based on the total number of grains in the copper foil, the number of grains with a grain size greater than 500 nm accounts for less than or equal to 5%; (4) Based on the total number of grains in the copper foil, the number of equiaxed grains or quasi-equiaxed grains accounts for greater than or equal to 80%, and the ratio a1 of the length of the major axis to the minor axis of the equiaxed grains or quasi-equiaxed grains satisfies: 1≤a1<2; (5) Based on the total number of grains in the copper foil, the number of columnar grains accounts for less than 10%, and the ratio a2 of the length of the major axis to the minor axis of the columnar grains satisfies: a2>2; (6) The crystal plane diffraction intensity of the (111) texture in the copper foil accounts for 60% to 85% of the total crystal plane diffraction intensity of the (111) texture, (200) texture, (220) texture, (311) texture, and (222) texture in the copper foil; (7) The copper foil has a first surface and a second surface opposite to each other, the thickness of the copper foil is denoted as H, the area from the first surface of the copper foil to a thickness range of 0.2H-0.5H is denoted as the first area of the copper foil, and the area from the second surface of the copper foil to a thickness range of 0.2H-0.5H is denoted as the second area of the copper foil, and the absolute value of the difference between the average grain size of the grains in the first area and the average grain size of the grains in the second area is less than or equal to 150nm; (8) Based on the total number of grains in the copper foil, the number of nanotwin grains accounts for 65% to 90%.
3. The current collector according to claim 1 or 2, characterized in that: The copper foil meets one or more of the following characteristics: (1) The maximum surface roughness of the copper foil is less than or equal to 3 μm; (2) The thickness H of the copper foil satisfies: 3 μm ≤ H ≤ 15 μm; (3) Under the test conditions of room temperature, sample thickness of 6±0.2 μm, and tensile speed of 50±0.5 mm / min, the tensile strength of the copper foil is greater than or equal to 600 MPa and the elongation at break of the copper foil is greater than or equal to 4%; (4) Under the test conditions of room temperature, sample thickness of 6±0.2 μm, and tensile speed of 50±0.5 mm / min, the tensile strength of the copper foil is 700 MPa-1500 MPa; the elongation at break of the copper foil is 4.5%-10%.
4. A pole piece, characterized in that: The pole piece comprises the current collector according to any one of claims 1 to 3.
5. A secondary battery, characterized in that: The invention comprises the pole piece as claimed in claim 4.
6. The secondary battery according to claim 5, characterized in that: The maximum expansion force of the secondary battery cell is greater than or equal to 1000 kgf.
7. The secondary battery according to claim 5, characterized in that: The maximum expansion force of the secondary battery cell is greater than or equal to 2500 kgf.
8. The secondary battery according to claim 5, characterized in that: The maximum expansion force of the secondary battery cell is greater than or equal to 4000 kgf.
9. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 5 to 8.
10. A method for preparing copper foil, characterized in that: The copper foil is prepared by electroplating, which specifically includes periodically applying current to an electrolyte so that copper ions in the electrolyte are reduced and deposited to form copper foil. The average particle size of the grains in the copper foil is 50nm-400nm, and based on the total number of grains in the copper foil, the number of nanotwin grains accounts for greater than or equal to 60%.
11. The preparation method according to claim 10, characterized in that: The current is a pulse current, and the pulse current includes one or more of a square wave pulse current, a sine wave pulse current, a triangle wave pulse current, and a sawtooth wave pulse current.
12. The preparation method according to claim 10 or 11, characterized in that: The electrolyte includes additives, and the additives include one or more of a leveling agent, a wetting agent, and a brightener.
13. The preparation method according to any one of claims 10 to 12, characterized in that: The additives include leveling agents, wetting agents and brighteners.
14. The preparation method according to claim 12 or 13, characterized in that: The electrolyte satisfies one or more of the following conditions: (1) The concentration of the leveling agent in the electrolyte is 20 mg / L-300 mg / L; (2) The concentration of the leveling agent in the electrolyte is 50 mg / L-150 mg / L; (3) The concentration of the wetting agent in the electrolyte is 10 mg / L-200 mg / L; (4) The concentration of the wetting agent in the electrolyte is 30 mg / L-100 mg / L; (5) The concentration of the brightener in the electrolyte is 10 mg / L-200 mg / L; (6) The concentration of copper ions in the electrolyte is 30 g / L-100 g / L; (7) The concentration of copper ions in the electrolyte is 45 g / L-75 g / L; (8) The concentration of chloride ions in the electrolyte is 10 mg / L-80 mg / L; (9) The pH of the electrolyte is 2.5-4.
4.
15. The preparation method according to any one of claims 12 to 14, characterized in that: The leveling agent includes one or more of gelatin and Janus Green; the wetting agent includes one or more of hydroxyethyl cellulose and polyethylene glycol; the brightening agent includes one or more of sodium polydisulfide propane sulfonate, sodium 3-mercapto-1-propane sulfonate, and thiourea.
16. The preparation method according to any one of claims 12 to 15, characterized in that: Such wetting agents include hydroxyethylcellulose and polyethylene glycol.
17. The preparation method according to any one of claims 14 to 16, characterized in that: The mass concentration ratio of the copper ion to the leveling agent is 500:1-4500:1; and / or, The mass concentration ratio of the copper ion to the brightener is 300:1-6000:
1.
18. The preparation method according to any one of claims 12 to 17, characterized in that: The electrolyte includes gelatin with a concentration of 20 mg / L-150 mg / L, polyethylene glycol with a concentration of 15 mg / L-100 mg / L, hydroxyethyl cellulose with a concentration of 10 mg / L-80 mg / L, sodium polydisulfide dipropane sulfonate with a concentration of 15 mg / L-150 mg / L, copper ions with a concentration of 45 g / L-90 g / L, and chloride ions with a concentration of 10 mg / L-80 mg / L.
19. The preparation method according to any one of claims 11 to 18, characterized in that: The peak current density of the pulse current is I, in A / dm 2 ; The current duty cycle of the pulse current is s, and the peak current density I and the duty cycle s satisfy: 2A / dm 2 ≤I×s≤18A / dm 2 .
20. The preparation method according to any one of claims 11 to 19, characterized in that: The electroplating method satisfies one or more of the following conditions: (1) The peak current density I of the pulse current satisfies: 3.3A / dm 2 ≤I≤333A / dm 2 ; (2) The duty cycle s of the pulse current satisfies: 2%≤s≤50%; (3) The pulse width of the pulse current is 1 ms to 50 ms; (4) The distance between the cathode electrode and the anode electrode is 15 mm to 20 mm; (5) The deposition temperature is 45°C-60°C; (6) The deposition time is greater than or equal to 80 seconds.
21. The preparation method according to any one of claims 11 to 20, characterized in that: The electroplating method specifically includes periodically applying a pulse current to the electrolyte so that the copper ions in the electrolyte are reduced and deposited; wherein the peak current density I of the pulse current satisfies 100A / dm 2 ≤I≤180A / dm 2 The duty cycle s of the pulse current satisfies: 2%≤s≤10%, and the deposition time is 80s-250s.
22. The preparation method according to any one of claims 10 to 21, characterized in that: The preparation method is a continuous production method.
23. A copper foil, characterized in that: The copper foil is prepared by the preparation method described in any one of claims 10 to 22.
24. The copper foil according to claim 23, characterized in that The maximum width of the copper foil is greater than or equal to 1.5 meters, and / or the maximum length of the copper foil is greater than or equal to 10,000 meters.
Citation Information
Patent Citations
Method for preparing nano twin crystal copper layer by high-frequency pulse
CN110592621A
Nano twin crystal copper thin film material and preparation method and application thereof
CN112779572A
Nanotwin copper components
CN112941586A
Electro-deposition of NANO twinned copper structures
CN113260739A
Ultrathin multi-layer structure type nano twin crystal copper foil as well as preparation method and application thereof
CN114908386A
Cited By
Circuit board and manufacturing method thereof
CN121038099A
Current collector, electrode sheet, secondary battery, electric device, copper foil, and preparation method for copper foil
EP4723250A1
Current collector, electrode sheet, secondary battery, electric device, copper foil, and preparation method for copper foil
WO2025161365A1
Battery cell, battery apparatus and electrical apparatus
WO2026170657A1